Concept of obesity in Unani medicine: historical perspectives, etiology, pathophysiology and therapeutic approaches - Sughra, Anam; Khan, Tariq N. (International Journal of Research in Medical Sciences, 2025)
Obesity is a chronic lifestyle disease caused by unhealthy dietary habits and inadequate exercise, remains a significant public health concern due to its widespread occurrence. This article explained obesity from both the Unani system of medicine and contemporary medical perspectives. The aim of this research is to bring together traditional and modern perspective to comprehensive understanding of obesity. A comprehensive literature review was conducted, to explore the historical context, etiopathogenesis, risk factors, signs, symptoms, complication and management strategies of obesity through the analyzing of authentic text books and manuscripts of Unani and contemporary scientific research. A search was conducted on Google Scholar, Sci Hub, PubMed and Scopus, using keywords such as Obesity, Mizāj, Temperament, Sū’-i-Mizāj, and Farbahi. This review found that imbalanced in diet and physical activity leads to Sū’-i-Mizāj Barid, which is responsible for obesity. The detailed concept of obesity as per both Modern and Unani perspectives have been described. Additionally, the therapeutic measures of obesity with reference to the Unani concept also mentioned that may play a pivotal role in the prevention and management of obesity. Both approaches emphasize the importance of dietary habits, physical activity and other factors related with obesity. By combining traditional and contemporary understandings, potential combinations of methods may provide more thorough and efficient ways for managing obesity. Focusing on natural remedies and lifestyle changes in Unani medicine offers a viable path for future research and treatment strategies.